Biochemistry: a short course - Tymoczko, John L; Tymoczko, John L.; Berg, Jeremy M.; Stryer Lubert (New York, W H Freeman, 2013)
Derived from the best-selling classic text originated by Lubert Stryer and continued by John Tymoczko and Jeremy Berg, Biochemistry: A Short Course focuses on the major topics taught in a one-semester biochemistry course. With its short chapters and relevant biological and clinical examples, this text shows biochemistry as a part of students' everyday lives. Offering the same signature writing style and physiological emphasis as the full-length text, this briefer book focuses on the major topics by eliminating details of enzyme mechanisms and organic chemistry, and by removing extraneous and advanced topics. Coverage is broken into short chapters for ease of use. Numerous examples and photos of biochemistry in action show students that biochemistry is part of everything they do and experience. Students learn a biochemical concept, then see how that concept is applied in the real world. Clinical Insights show how our understanding of biochemical concepts influences an aspect of a disease or its cure, and Biological Insights show how simple changes in biochemical processes can have dramatic effects. The Second Edition has been fully updated with coverage of recent developments in biochemistry and human health. New Metabolism in Context sections show how new information on the role of leptins in hunger and satiety has changed the way biochemists think about obesity and diabetes. In addition to diet and obesity, other Metabolism in Context features focus on metabolism and cancer, and metabolism and exercise. The Experimental Techniques chapters (available on the companion website) have also been updated and expanded, exploring important techniques used by biochemists in the past as well as new technologies with which biochemists make discoveries in present-day laboratories.
Appendices A.1-16p.; Glossary B.1-16p.; Index I.1-31p.
Keywords: Biomolecules; Enzyme actions; Genetic formation; Metabolism; Biochemistry